Promoting civility in nursing education and practice: A systematic literature review - Juneivent Saputra Datu Hanggamara; Leny Felinia; Putry Sisilia Witak; Ni Gusti Ayu Eka; Windy Sapta Handayani Zega (Malahayati International Journal of Nursing and Health Science, 2022)
Background: Civility is an attitude of mutual respect and tolerance for differences that influences the professionalism of a nurse. However, there is a rise in incivility in nursing, including aggressive behavior, a lack of discipline, and failure to follow rules. Nursing education and practice are critical for promoting civil behavior through effective communication, conflict management, and resolution.Purpose: To determine strategies for promoting civility in nursing education and practice.Method: This study utilized a simplified approach to conduct a systematic review of the literature. The databases used were PubMed, Google Scholar, Science Direct (Elsevier), and EBSCO. Civility, incivility, promoting civility, and nursing were used as keywords.Results: This study identified two major themes: "strategy for promoting civility" and "impact of promoting civility." Active discussion, Problem-Based Learning (PBL), Civility Journal Club (CJC), role modeling, and self-reflection were all used to increase civility. The strategy's impact was measured in terms of individual capacity and interpersonal interaction.Conclusion: It is critical to promote civility in nursing education and practice. Nursing educators must facilitate activities that promote polite behavior, and nursing practice institutions must assist nurses in developing civility through civility promotion activities. Additional research can be conducted to ascertain the efficacy of civility promotion strategies in nursing as a means of promoting polite behavior.